Hospital‐in‐the‐Home experience of first 23 COVID‐19 patients at a regional NSW hospital. Issue 10 (18th September 2020) - Lwin, Nilar; Burgess, Jenny; Johnston, Claire; Johnson, Nyomie; Chung, Steven
Abstract: Ambulatory care is an important service for patients with the COVID‐19 infection especially in a regional area where most of the patients underwent home isolation. Escalation of treatment and timely transition to inpatient care are critical when COVID‐19 patients deteriorate. Equally important is ensuring transfer into facility is carried out in a well‐planned, safe manner to prevent exposure to health care professionals as well as other inpatients. This study is a summary of our COVID Hospital‐in‐the‐Home (HITH) service and clinical presentation of COVID‐19 patients.